Estimasi Gaya Dorong Dari Motor Brushless Dengan Variasi Propeller Untuk Pesawat Model X-UAV Mini Talon Dengan Menggunakan Pengukur Massa - Ananda Rafi Rijalul Awwal; Mufti Arifin; Endah Yuniarti (FTK UNSURYA, 2020)
One that affects aircraft performance is the thrust. The thrust is determined according to the requirements of the aircraft itself. This study uses a thrust test stand that uses a mass gauge as a thrust gauge, using two brushless motors and five propellers to determine the optimal thrust for X-UAV Mini Talon aircraft flying missions. The thrust required by the X-UAV Mini Talon aircraft - is known to be 0.6755 N for cruise flights and 4.979 N for take-off aircraft. After testing, the smallest thrust is produced by the configuration of the DYS 2826-13 brushless motor with a 5x3 inch propeller, while the biggest thrust by the RacerStar BR2212 brushless motor with a 10x6 inch propeller. Compared to calculations with propeller static thrust equation, the difference in thrust in testing with propeller static thrust ranges from 15% to 25%. Therefore, the optimal configuration for flying cruising is the DYS 2826-13 brushless motor with a 5x3 inch propeller, which produces a thrust of 0.988 N. Then, for the optimal configuration take-off is the Brushless DYS 2826-13 with a 9x5 inch propeller, which results in a thrust of 6,151. The configuration above was chosen because it is more efficient, with smaller current requirements compared to other configurations with more or less equivalent thrust.